ADVANTAGES AND DISADVANTAGES OF FOOD ESTATE POLICY FOR RURAL COMMUNITIES - Eri Mardiani; Rizal R. Manullang; Nanang Qosim; Iwan Harsono; Zulham (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
There are two opposing camps who have their own arguments which are almost equally strong, namely the function of the Food Estate policy in order to increase food security in Indonesia. However, on the other hand, this policy has the potential to damage the environment. This research is qualitative research with a descriptive approach related to Food Estate as a solution to overcoming food scarcity or whether it is a wrong policy that can damage the surrounding environment. The result in this article show several things regarding the Food Estate policy have more advantages or disadvantages as follows: 1. Food Estate can increase food security in Indonesia 2. Food Estate can also cause less damage to the environment if it has a print that protects the environment and achieves sustainable development goals.